Impoliteness strategies applied in political debates in Lithuania and USA - Žurauskaitė, Eglė (Vilnius University Open Series, 2023)
The aim of this study is to reveal which impoliteness strategies politicians use during electoral TV debates in Lithuania and the USA. To achieve this aim, four debates were analyzed using a quantitative analysis method. The total duration of the debates analyzed was 360 minutes. The study revealed that politicians in Lithuania and the USA primarily use indirect impoliteness strategies, directed towards positive or negative faces of their opponents. Analysis also revealed that politicians in the USA use direct impoliteness strategies 2.4 times more often than politicians in Lithuanian TV debates. The strategy of off-record impoliteness was used the least during debates in each country. Analysis of how impoliteness strategies are expressed revealed that politicians in the USA mostly express impoliteness as statements, while Lithuanian politicians express it using various language resources: presenting it as their opinion, doubt, etc.
Keywords: impoliteness; debates; impoliteness strategies; expressing impoliteness strategies